Medical sharp box and preparation method thereof

CN122706038BActive Publication Date: 2026-10-20HUBEI KEMET MEDICAL & SANITARY MATERIALS CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611195770.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-07
Publication Date
2026-10-20
Estimated Expiration
2046-08-07

AI Technical Summary

Technical Problem

[0005]本发明的主要目的是提出一种医用利器盒及其制备方法,旨在解决现有聚丙烯医用利器盒在实际使用和储运过程中,因材料自身力学性能局限而无法兼顾抗穿刺与低温抗冲击耐跌落韧性,导致盒体在受到锐器顶压或碰撞冲击时极易发生刺穿泄露的问题

Benefits of technology

本发明提供了一种医用利器盒,通过科学配比多元组分,协同提升制品力学性能。本发明采用均聚聚丙烯、共聚聚丙烯与马来酸酐接枝聚丙烯复配树脂体系,依托均聚聚丙烯提供基础刚性与结构强度,共聚聚丙烯改善基体韧性与抗冲击性能,马来酸酐接枝聚丙烯优化碳酸钙与聚烯烃基体的相容性;其中,改性碳酸钙作为功能组分,可显著提升利器盒的抗穿刺和低温抗冲击性能,改性碳酸钙通过在含有刚性基团和羟基的醛类化合物中的酚羟基与环氧化天然橡胶发生开环反应,生成新的活性羟基,在熔融过程中,生成新的活性羟基能够与体系中的马来酸酐接枝聚丙烯发生酯化反应或形成强极性相互作用,显著增强了无机碳酸钙与聚烯烃基体之间的界面结合力,解决了碳酸钙填料与聚丙烯基体界面结合力弱、易界面剥离、应力集中的行业痛点,该结构可大幅增强无机-有机两相界面结合强度,同步提升利器盒的整体结构强度、抗穿刺能力与低温抗冲击韧性,有效抑制盒体受锐器顶压穿刺、低温转运、意外跌落、剧烈碰撞时出现的裂纹扩展、基体开裂及废液泄漏问题,让利器盒在医院临床使用、低温储运、堆叠存放等复杂工况下,始终具备优异、稳定的耐穿刺性能与抗冲击韧性,极大提升了医用利器盒的使用安全性与服役稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122706038B_ABST
    Figure CN122706038B_ABST
Patent Text Reader

Abstract

The application discloses a medical sharp implement box and a preparation method thereof, and belongs to the technical field of medical supplies. The medical sharp implement box is formed by injection molding of modified polypropylene composite pellets, and the modified polypropylene composite pellets comprise the following components in parts by mass: 30-50 parts of homopolymer polypropylene, 10-30 parts of copolymer polypropylene, 10-20 parts of modified calcium carbonate, 3-10 parts of maleic anhydride grafted polypropylene, 0.1-1 part of color master batch, 0.5-1.5 parts of lubricant, and 0.5-1 part of antioxidant. The technical problem that the box body is easily punctured and leaked when subjected to sharp implement pressure or impact is effectively solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of medical supplies technology, specifically to a medical sharps box and its preparation method. Background Technology

[0002] Medical sharps containers are specialized protective containers used in medical institutions to store high-risk medical sharps such as syringes, infusion sets, discarded blades, and suture needles. Because the waste they contain poses a significant risk of puncture wounds and biotoxicity, the structural integrity and physical protective performance of these containers directly impact the safety of medical, transport, and disposal personnel. Therefore, relevant standards set stringent mandatory standards for the puncture resistance and drop impact resistance of medical sharps containers, which are crucial for ensuring the safe disposal of medical waste.

[0003] Polypropylene has become the mainstream matrix resin for medical sharps containers due to its advantages of being non-toxic, sterile, chemically stable, easy to injection molded, and cost-effective. However, pure polypropylene has significant mechanical property defects that make it difficult to meet high-standard usage requirements: on the one hand, pure polypropylene lacks rigid support and is prone to local yielding deformation when subjected to pressure from medical sharps, exhibiting weak puncture resistance and failing to avoid the risk of sharps piercing the container wall and pathogen leakage; on the other hand, polypropylene exhibits significant low-temperature brittleness, especially highly crystalline homopolymer polypropylene, where molecular chain movement is hindered at low temperatures, resulting in a significant decrease in toughness. During storage and transportation in northern winters and cold chain transfers, it is extremely prone to breakage and damage from drops and impacts, leading to safety hazards such as medical waste leakage and pollution.

[0004] Currently, the industry mainly modifies polypropylene through two methods: elastomer toughening and inorganic filler filling. While adding rubber elastomers such as POE and EPDM can improve the material's low-temperature impact toughness, it will significantly reduce the matrix stiffness and hardness, resulting in insufficient rigidity of the sharps box, easy deformation and collapse, and a significant decrease in puncture resistance. Calcium carbonate has the characteristics of low cost, excellent rigidity, and strong chemical stability, making it an ideal filler for polypropylene. However, calcium carbonate has extremely poor interfacial compatibility with non-polar polypropylene, and it is prone to agglomeration, causing stress concentration, deteriorating the material's impact toughness, and aggravating brittle cracking of the box. Therefore, surface functionalization modification of calcium carbonate to optimize its interfacial bonding with the resin matrix and prepare a high-safety medical sharps box that combines high puncture resistance, low-temperature drop resistance, and no brittle cracking is a technical pain point that urgently needs to be solved in this field. Summary of the Invention

[0005] The main objective of this invention is to propose a medical sharps box and its preparation method, aiming to solve the problem that existing polypropylene medical sharps boxes, due to the limitations of the material's own mechanical properties, cannot simultaneously achieve puncture resistance and low-temperature impact and drop resistance, resulting in the box being easily punctured and leaking when subjected to pressure from sharp objects or impact.

[0006] To achieve the above objectives, the present invention proposes a medical sharps box, which is injection molded from modified polypropylene composite granules. The modified polypropylene composite granules comprise the following components in parts by weight: 30-50 parts homopolymer polypropylene, 10-30 parts copolymer polypropylene, 10-20 parts modified calcium carbonate, 3-10 parts maleic anhydride grafted polypropylene, 0.1-1 parts color masterbatch, 0.5-1.5 parts lubricant, and 0.5-1 parts antioxidant.

[0007] According to this application, by melt blending and synergistic effect of homopolymer polypropylene, copolymer polypropylene, modified calcium carbonate and maleic anhydride grafted polypropylene in the above-mentioned specific mass ratio, the resulting medical sharps box achieves a good balance of rigidity and toughness in mechanics. While ensuring that the box body has excellent puncture resistance, it also gives the box body low-temperature impact resistance, thus solving the technical problem that the sharps box is prone to cracking and leakage during low-temperature transportation or collision.

[0008] First, this invention uses homopolymer polypropylene and copolymer polypropylene to form a compound. The highly regular crystalline segments of homopolymer polypropylene form a strong rigid skeleton, ensuring the overall support of the sharp object box and its excellent resistance to bending creep. Meanwhile, the presence of flexible copolymer segments in copolymer polypropylene injects an elastic energy buffer into the matrix. The compounding of the two ensures that the box does not yield when it is filled with heavy objects or stacked, and also provides the material with excellent resistance to impact deformation.

[0009] Based on the above technical solutions, the preferred method for preparing the modified calcium carbonate is as follows: (1) Calcium carbonate is surface modified with an aminosilane coupling agent to obtain surface-aminated calcium carbonate; (2) Surface-aminated calcium carbonate undergoes a Schiff base reaction with a compound containing both rigid groups and hydroxyl aldehydes to obtain functionalized calcium carbonate; (3) Functionalized calcium carbonate undergoes a ring-opening reaction with epoxidized natural rubber to obtain modified calcium carbonate.

[0010] Based on the above technical solutions, preferably, the compound containing both rigid groups and hydroxy aldehydes is at least one of vanillin, salicylaldehyde, p-hydroxybenzaldehyde, and 8-hydroxyquinoline-2-carboxaldehyde.

[0011] Based on the above technical solutions, preferably, the mass ratio of aminosilane coupling agent to calcium carbonate in step (1) is 5-10:100.

[0012] Based on the above technical solutions, preferably, in step (2), the mass ratio of surface-aminated calcium carbonate and compounds containing both rigid groups and hydroxy aldehydes is 100:10-15; the compounds containing both rigid groups and hydroxy aldehydes are at least one of vanillin, salicylaldehyde, p-hydroxybenzaldehyde, and 8-hydroxyquinoline-2-carboxaldehyde.

[0013] Based on the above technical solutions, preferably, the mass ratio of functionalized calcium carbonate and epoxidized natural rubber in step (3) is 100:8-15.

[0014] The preparation of modified calcium carbonate in this invention uses inorganic calcium carbonate as the core. The surface of calcium carbonate is modified with an aminosilane coupling agent to introduce active amino groups, which is beneficial to subsequent reactions. Then, these surface amino groups are used to perform Schiff base reactions with aldehyde compounds containing rigid groups and hydroxyl groups to graft highly rigid aromatic rings or heterocyclic structures onto the surface of calcium carbonate in situ. Finally, the hydroxyl groups on the aldehyde compounds containing rigid groups and hydroxyl groups undergo ring-opening reactions with epoxidized natural rubber to generate new active hydroxyl groups.

[0015] In this invention, calcium carbonate is modified to possess both rigid support and impact energy dissipation properties. The imine bond (-N=CH-) in the Schiff base forms a conjugated system with adjacent benzene rings / heterocyclic rings, improving the overall chemical stability of the rigid segment and making it less prone to degradation or breakage under both high-temperature processing and low-temperature use conditions. Simultaneously, the conjugated structure facilitates the regular arrangement of benzene rings on the calcium carbonate surface. When external sharp impact or low-temperature impact generates stress, the stress wave is first transmitted from the PP matrix to the interface. The rigid aromatic rings or heterocyclic structures adjacent to the calcium carbonate surface possess high conjugated stability and significant steric hindrance, dispersing point stress into planar stress and preventing stress concentration at local sites on the calcium carbonate surface, which could lead to interfacial cracking. Furthermore, the benzene rings act as a bridge connecting the inorganic filler and the rubber phase, further transmitting stress outward to the flexible segments of the epoxidized natural rubber. The flexible segments dissipate energy through elastic deformation via segment extension and curling, inhibiting crack propagation. Meanwhile, the hydroxyl groups generated after the ring-opening of epoxidized natural rubber can undergo esterification reactions or form strong polar interactions with the anhydride groups in maleic anhydride-grafted polypropylene, thereby improving the interfacial bonding force between modified calcium carbonate and the polypropylene matrix, reducing the risk of filler agglomeration and phase separation of rubber, and enabling the sharps box material to obtain good low-temperature impact toughness while maintaining high rigidity and puncture resistance.

[0016] Preferably, the degree of epoxidation of the epoxidized natural rubber is 20-50 mol%.

[0017] This invention limits the epoxidation degree of epoxidized natural rubber to 20-50 mol%. If the epoxidation degree is too low, the number of epoxy groups on the epoxidized natural rubber molecular chain is insufficient. On the one hand, the ring-opening reaction sites between epoxy groups and phenolic hydroxyl groups are scarce, resulting in a low grafting rate of epoxidized natural rubber on the calcium carbonate surface and incomplete coverage of the flexible layer. On the other hand, the number of newly generated active hydroxyl groups after ring opening is insufficient, limiting the efficiency of the subsequent esterification reaction with the anhydride groups in maleic anhydride-grafted polypropylene, reducing the interfacial chemical bond density, and failing to effectively improve the interfacial bonding force between the filler and the matrix. If the epoxidation degree is too high, the epoxy group density is too large. Although this is beneficial for the ring-opening reaction with phenolic hydroxyl groups, the flexibility of the epoxidized natural rubber molecular chain will decrease significantly, the glass transition temperature will increase sharply, the elastic characteristics of the rubber will weaken, and the impact energy dissipation capacity will decrease. At the same time, excessive epoxy groups may undergo side reactions such as self-crosslinking under the high-temperature shear conditions of melt processing, causing the flexible layer on the filler surface to harden and become brittle, which in turn damages the low-temperature impact toughness of the material.

[0018] Preferably, the masterbatch is a yellow masterbatch, preferably iron oxide yellow and / or vanadium yellow.

[0019] Based on the above embodiments, the color masterbatch can provide medical sharps boxes with a clear, eye-catching appearance that meets the industry standard for medical waste safety warning labels.

[0020] Preferably, the lubricant is polyethylene wax.

[0021] Based on the above embodiments, the lubricant can significantly improve the melt flowability of the high-filler system during melt blending, and reduce the frictional resistance between the material and the screw and mold wall. It not only improves the uniform dispersion of modified calcium carbonate in the polypropylene matrix, but also eliminates microscopic surface defects such as melt cracking and flow marks that may occur on the surface of the toolbox during injection molding, avoiding stress concentration and premature cracking caused by microscopic surface gaps, resulting in a denser and smoother surface.

[0022] Preferably, the antioxidant is at least one of antioxidant 1076, antioxidant 1010, and antioxidant 264.

[0023] Based on the above embodiments, the antioxidant can efficiently capture free radicals generated by heating, strong shearing or light exposure in the blended system during melt processing and later service of the weapon box, thereby blocking the thermo-oxidative degradation process of the polymer chain.

[0024] The present invention also provides a method for preparing the above-mentioned medical sharps box, comprising the following steps: The medical sharps box is obtained by uniformly mixing homopolymer polypropylene, copolymer polypropylene, maleic anhydride grafted polypropylene, modified calcium carbonate, color masterbatch, lubricant, and antioxidant, followed by melt blending, granulation, and injection molding.

[0025] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention provides a medical sharps box that synergistically enhances the mechanical properties of the product through a scientifically formulated blend of multiple components. The invention employs a composite resin system of homopolymer polypropylene, copolymer polypropylene, and maleic anhydride-grafted polypropylene. Homopolymer polypropylene provides basic rigidity and structural strength, copolymer polypropylene improves the matrix toughness and impact resistance, and maleic anhydride-grafted polypropylene optimizes the compatibility between calcium carbonate and the polyolefin matrix. Modified calcium carbonate, as a functional component, significantly improves the puncture resistance and low-temperature impact resistance of the sharps box. Modified calcium carbonate undergoes a ring-opening reaction with epoxidized natural rubber through the phenolic hydroxyl groups in aldehyde compounds containing rigid groups and hydroxyl groups, generating new active hydroxyl groups. During the melting process, these new active hydroxyl groups can undergo esterification reactions or form strong polar interactions with the maleic anhydride-grafted polypropylene in the system, significantly… This design enhances the interfacial bonding between inorganic calcium carbonate and the polyolefin matrix, addressing industry pain points such as weak interfacial bonding, easy interface peeling, and stress concentration between calcium carbonate filler and polypropylene matrix. This structure significantly strengthens the interfacial bonding strength between the inorganic and organic phases, simultaneously improving the overall structural strength, puncture resistance, and low-temperature impact toughness of the sharps container. It effectively suppresses crack propagation, matrix cracking, and waste liquid leakage when the container is punctured by sharp objects, transported at low temperatures, accidentally dropped, or subjected to severe impacts. This ensures that the sharps container maintains excellent and stable puncture resistance and impact toughness under complex conditions such as clinical use in hospitals, low-temperature storage and transportation, and stacking, greatly improving the safety and service stability of medical sharps containers. Attached Figure Description

[0026] The accompanying drawings, which are incorporated in and form part of this specification, illustrate embodiments consistent with this application and, together with the description, serve to explain the principles of this application.

[0027] Figure 1 Infrared spectrum of unmodified calcium carbonate; Figure 2 Infrared spectrum of modified calcium carbonate. Detailed Implementation

[0028] To avoid unnecessary details, unless otherwise specified, all items used in the following examples are commercially available products, and all methods used are conventional methods unless otherwise specified.

[0029] The sources of some of the raw materials used in this invention are as follows: Homopolymer polypropylene, grade polypropylene V30G.

[0030] Copolymer polypropylene, grade polypropylene K8003.

[0031] Epoxidized natural rubber, grade ENR-25.

[0032] Polyethylene wax, Honeywell AC-6.

[0033] Calcium carbonate, 325 mesh.

[0034] Iron oxide yellow, Linhui Group's high-temperature resistant iron oxide yellow pigment series 3419M.

[0035] Example 1 A method for preparing a medical sharps container includes the following steps: 40 parts of homopolymer polypropylene, 25 parts of copolymer polypropylene, 8 parts of maleic anhydride-grafted polypropylene, 12.5 parts of modified calcium carbonate, 0.8 parts of iron oxide yellow, 1.2 parts of polyethylene wax, and 0.8 parts of antioxidant 1010 were dried separately and then mixed evenly. The mixture was then fed into a twin-screw extruder for melt blending and extrusion granulation. The temperatures of the extruder's first to seventh zones were 170℃, 180℃, 190℃, 200℃, 205℃, 200℃, and 190℃, respectively, with the die head temperature at 190℃. After cooling, pelletizing, and drying, modified polypropylene composite granules were obtained. The modified polypropylene composite granules were then injection molded in an injection molding machine at a melting temperature of 200℃ and a mold temperature of 50℃ to obtain a medical sharps box.

[0036] The modified calcium carbonate is prepared as follows: 100 parts of dry calcium carbonate were ultrasonically dispersed in 800 parts of 90wt% ethanol aqueous solution. 8.5 parts of KH550 were added, and the pH of the system was adjusted to 5.0 using dilute acetic acid solution. The mixture was stirred at 50℃ for 4 hours. The solid was collected by filtration, washed with ethanol, and dried to obtain surface-aminated calcium carbonate. 100 parts of surface-aminated calcium carbonate were dispersed in 800 parts of anhydrous ethanol. 12.5 parts of p-hydroxybenzaldehyde and 4A molecular sieve in a mesh bag were added. The mixture was heated at 60℃ for 12 hours. The mesh bag was then removed. The solid product was collected by bag filtration, washed with ethanol, and dried to obtain functionalized calcium carbonate. 100 parts of functionalized calcium carbonate were dispersed in 1000 parts of toluene, and 10.8 parts of epoxidized natural rubber, 0.5 parts of 1,5,7-triazabicyclo[4.4.0]dec-5-ene and 1 part of benzyltrimethylammonium chloride were added. The mixture was heated to 110°C under nitrogen protection for 9 hours. After the reaction was completed, it was cooled to room temperature, and the solid product was collected by suction filtration, washed with ethanol, and dried to obtain modified calcium carbonate.

[0037] like Figure 1 As shown, unmodified calcium carbonate at 1420 cm⁻¹ -1 The strong absorption peak at this point can be attributed to CO3. 2- Asymmetric stretching vibration; at approximately 874 cm -1 and 712 cm -1The presence of distinct absorption peaks at 3400 cm⁻¹ corresponds to the out-of-plane and in-plane bending vibrations of the carbonate ion, indicating that the sample has a typical calcium carbonate structure. Only a weak and broad peak appears near 3400 cm⁻¹, which may originate from a small amount of water adsorbed on the surface of the calcium carbonate. like Figure 2 As shown, modified calcium carbonate at approximately 3430 cm⁻¹ -1 A broad peak of hydroxyl stretching vibration appears at 2925 cm⁻¹. -1 and 2855cm -1 An aliphatic CH stretching vibration peak appeared nearby. Notably, at 1638 cm⁻¹... -1 The presence of clear, weak to moderate intensity absorption peaks at approximately 1450, 874, and 713 cm⁻¹ can be attributed to the stretching vibration of the C=N bond in the Schiff base structure, indicating a condensation reaction between the surface amino group and p-hydroxybenzaldehyde. -1 The strong absorption peaks at 1000–1100 cm⁻¹ correspond to the asymmetric stretching and bending vibrations of the carbonate ion, respectively, indicating that the main structure of calcium carbonate is still retained after modification. -1 The presence of weak to moderate intensity absorption peaks within the range can be attributed to the stretching vibrations of Si-O-Si, Si-O-Ca, and COC bonds. The peak intensity is significantly lower than that of the main calcium carbonate peak, which is consistent with the characteristics of a small amount of silane coupling agent and epoxidized natural rubber grafted onto the surface of inorganic fillers.

[0038] Example 2 A method for preparing a medical sharps box is similar to that in Example 1, except that in the modified calcium carbonate preparation step, p-hydroxybenzaldehyde is replaced with 8-hydroxyquinoline-2-carboxaldehyde.

[0039] Example 3 A method for preparing a medical sharps box is similar to that in Example 1, except that in the modified calcium carbonate preparation step, p-hydroxybenzaldehyde is replaced with vanillin.

[0040] Comparative Example 1 A method for preparing a medical sharps box is similar to that in Example 1, except that the epoxidized natural rubber in the modified calcium carbonate is a physical mixture.

[0041] The modified calcium carbonate is prepared as follows: 100 parts of dry calcium carbonate were ultrasonically dispersed in a mixed solution of 800 parts of 90wt% ethanol and water. 8.5 parts of KH550 were added, and the pH of the system was adjusted to 5.0 using dilute acetic acid solution. The mixture was stirred at 50℃ for 4 hours. The solid was collected by filtration, washed, and dried to obtain surface-aminated calcium carbonate. 100 parts of surface-aminated calcium carbonate were dispersed in 800 parts of anhydrous ethanol. 12.5 parts of p-hydroxybenzaldehyde and an appropriate amount of 4A molecular sieve in a mesh bag were added. The mixture was heated at 60℃ for 12 hours. The mesh bag was removed, the solid product was collected by filtration, washed, and dried to obtain functionalized calcium carbonate. 100 parts of functionalized calcium carbonate and 10.8 parts of epoxidized natural rubber were mixed and stirred evenly to obtain modified calcium carbonate.

[0042] Comparative Example 2 A method for preparing a medical sharps box is similar to that in Example 1, except that the p-hydroxybenzaldehyde and epoxidized natural rubber in the modified calcium carbonate are physically mixed.

[0043] The modified calcium carbonate is prepared as follows: 100 parts of dry calcium carbonate were ultrasonically dispersed in a mixed solution of 800 parts of 90wt% ethanol and water. 8.5 parts of KH550 were added, and the pH of the system was adjusted to 5.0 using dilute acetic acid solution. The mixture was stirred at 50℃ for 4 hours. The solid was collected by filtration, washed, and dried to obtain surface-aminated calcium carbonate. 100 parts of surface-aminated calcium carbonate, 12.5 parts of p-hydroxybenzaldehyde, and 10.8 parts of epoxidized natural rubber were mixed and stirred evenly to obtain modified calcium carbonate.

[0044] Comparative Example 3 A method for preparing a medical sharps box is similar to that in Example 1, except that the modified calcium carbonate is prepared by grafting surface-aminated calcium carbonate with epoxidized natural rubber and then blending it with p-hydroxybenzaldehyde. The preparation method of the modified calcium carbonate is as follows: 100 parts of dry calcium carbonate were ultrasonically dispersed in 800 parts of 90wt% ethanol aqueous solution, 8.5 parts of KH550 were added, and the pH of the system was adjusted to 5.0 with dilute acetic acid solution. The mixture was stirred at 50℃ for 4 hours, and the solid was collected by filtration, washed with ethanol, and dried to obtain surface-aminated calcium carbonate. 100 parts of surface-aminated calcium carbonate were dispersed in 1000 parts of toluene, 10.8 parts of epoxidized natural rubber and 1 part of triethylamine were added, and the mixture was heated to 60℃ under nitrogen protection for 9 hours. After the reaction was completed, the mixture was cooled to room temperature, the solid product was collected by suction filtration, washed with ethanol, dried, and mixed with 12.5 parts of p-hydroxybenzaldehyde to obtain modified calcium carbonate.

[0045] Comparative Example 4 A method for preparing a medical sharps box is similar to that in Example 1, except that the calcium carbonate is not modified.

[0046] Performance testing The test subjects were the medical sharps boxes prepared in Examples 1-3 and Comparative Examples 1-4; Tensile property testing: Tensile properties were tested using a WDW universal tensile testing machine. Samples were placed in a testing environment of 23℃±2℃ and 50%±10% humidity for 48 hours. Tensile testing was conducted according to the national standard GB / T1040.1-2025 "Determination of Tensile Properties of Plastics - Part 1". Tensile strength (σ1) is the maximum load borne by the effective original cross-sectional area of ​​the specimen during the test. It is the maximum tensile stress that the material withstands until the specimen breaks under constant tensile rate. The calculation formula is: σ1 = p / (b·d) Where σ1 represents tensile strength in MPa; P represents maximum load (i.e., maximum force) in N; d represents specimen thickness in mm; and b represents specimen width in mm. The specimen dimensions are 150 mm × 20 mm × 3 mm. The tensile rate of the standard dumbbell-shaped specimen is 5 mm / min, and the gauge length of the specimen is 50 mm. Each group of specimens is tested 5 times, and the average value is taken based on the recorded valid data.

[0047] Puncture resistance test: Referring to ISO 23907-1:2019 standard, a microcomputer-controlled electronic universal testing machine with a puncture force testing fixture was used. A standard 21G medical syringe steel needle was selected and fixed on the moving crossbeam of the testing machine. A test sample with dimensions of 50mm×50mm×3mm was cut from the center of the bottom of the injection-molded sharps box in each embodiment and comparative example. The sample was horizontally fixed on the hollow clamp ring below. The universal testing machine was started, and the test needle was moved vertically downward at a constant speed of 100mm / min, piercing the center of the sample. The maximum load (i.e., puncture force, unit: N) displayed on the testing machine at the moment the needle completely pierced the sample was recorded. Five different locations were selected for testing for each sample, and the arithmetic mean was taken. Low-temperature impact resistance test: The medical sharps box prepared in Examples 1-3 and Comparative Examples 1-4 was cut into samples with a thickness of 4 mm, kept at -40℃ for 4 h, and the cantilever beam impact strength was tested according to ISO 180:2019. The test was performed in parallel for 3 times, and the average value of the results was taken. The test results are shown in Table 1. Table 1 Performance test results of high-strength medical sharps box As can be seen from the experimental results in Table 1, the medical sharps box prepared by this invention has good puncture resistance and low-temperature impact resistance.

[0048] The above are merely preferred embodiments of the present invention and do not limit the patent scope of the present invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the patent protection scope of the present invention.

Claims

1. A medical sharps box, characterized in that, The product is injection molded from modified polypropylene composite granules, wherein the modified polypropylene composite granules comprise the following components in parts by weight: 30-50 parts homopolymer polypropylene, 10-30 parts copolymer polypropylene, 10-20 parts modified calcium carbonate, 3-10 parts maleic anhydride grafted polypropylene, 0.1-1 parts color masterbatch, 0.5-1.5 parts lubricant, and 0.5-1 parts antioxidant. The modified calcium carbonate is prepared as follows: (1) Calcium carbonate is surface modified with an aminosilane coupling agent to obtain surface-aminated calcium carbonate; (2) Surface-aminated calcium carbonate undergoes a Schiff base reaction with a compound containing both rigid groups and hydroxyl aldehydes to obtain functionalized calcium carbonate; (3) Functionalized calcium carbonate undergoes a ring-opening reaction with epoxidized natural rubber to obtain modified calcium carbonate; The compound containing both rigid groups and hydroxy aldehydes is at least one of vanillin, salicylaldehyde, p-hydroxybenzaldehyde, and 8-hydroxyquinoline-2-carboxaldehyde. In step (3), the mass ratio of functionalized calcium carbonate to epoxidized natural rubber is 100:8-15.

2. The medical sharps box according to claim 1, characterized in that: In step (1), the mass ratio of aminosilane coupling agent to calcium carbonate is 5-10:

100.

3. The medical sharps box according to claim 1, characterized in that: In step (2), the mass ratio of surface-aminated calcium carbonate and compounds containing rigid groups and hydroxy aldehydes is 100:10-15.

4. The medical sharps box according to claim 1, characterized in that: The degree of epoxidation of the epoxidized natural rubber is 20-50 mol%.

5. The medical sharps box according to claim 1, characterized in that: The masterbatch is a yellow masterbatch.

6. The medical sharps box according to claim 1, characterized in that: The lubricant is polyethylene wax.

7. A method for preparing a medical sharps box according to any one of claims 1-6, characterized in that, Includes the following steps: The medical sharps box is obtained by uniformly mixing homopolymer polypropylene, copolymer polypropylene, maleic anhydride grafted polypropylene, modified calcium carbonate, color masterbatch, lubricant, and antioxidant, followed by melt blending, granulation, and injection molding.

Citation Information

Patent Citations

  • Polypropylene composition used in automobile air conditioner damper, and preparation method thereof

    CN103012960A

  • Modified polypropylene material for manufacturing yoghurt eight-connected cup and manufacturing method of modified polypropylene material

    CN115785570A